NET VALUE ADDED MONETARY MODEL FOR EVALUATING HUMAN CAPITAL - Franko Milost (European Scientific Journal, ESJ, 2014)
Man's work (human capital, employees) is an important element of the business process, however its value is not disclosed on the assets side of the classical balance sheet. In order to show human capital among assets one has to evaluate it. Evaluation can be made in monetary or non-monetary terms. Non-monetary models for evaluating human capital include organisational and behavioural variables. These variables are not expressed in monetary terms, however, based on changes in their quality, one can assume the increased or decreased value of human capital within the company. The value of non-monetary models should not be underestimated, however monetary models are of greater importance. This paper presents an original monetary model for evaluating human capital – a Net Value Added Model which is a result of several years of study in this field. The model is designed to calculate the value of a company's employees for their owners and to evaluate human capital as a whole. In this model, employees are considered to be the most important element of a business process; therefore their placing to the financial statements is essential.